TBCCO thin film microwave devices - Jenkins, A; Kale, K; Dew-Hughes, D; Edwards, D; Bramley, A; Grovenor, C (IEE, 1996)
Thallium based HTS thin films have been deposited on a variety of substrates, including single sided films on LaAlO3 and double sided films on MgO. Various microwave devices have been fabricated from such films including planar filters, high Q disk resonators and a tunable oscillator. This paper will report on experimental results for such devices and their integration with a cryocooler as well as presenting an overview of the current state of the TBCCO thin film program at Oxford.